PENGELOLAAN DANA DESA (DD) DI DESA SUNGAI ARA KECAMATAN PELALAWAN KABUPATEN PELALAWAN TAHUN 2016 - Julita, Elma; Yusri, Ali (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Village Fund Management must be done orderly because budgetary fund accepted by the village in the form of village fund is the very large amount. The rule about management of village finances including the village fund, as arranged in minister of domestic affairs no.113 of year 2014 about management of village finances, this is done to ensure controlling the village finances not inside “One Hand”, but inside in one team, with the manage system expected can be ensure from the happen of deviation. Furthermore, regulation of the Minister of Village number 21 of 2015 regarding the determination of the priority of the use of village funds in 2016, it aims to determine the program and activities for the implementation of the implementation of the authority of the right of origin and the local authority of the village scale funded by the Village Fund as a reference for the district / in compiling technical guidelines for the use of the Village Fund, and as a reference for the government in monitoring and evaluating the implementation of the use of the Village Fund.This research was done at Sungai Ara village Kecamatan Pelalawan Kabupaten Pelalawan. The method of this research was qualitative. The technique to collect the data was used by interview and documentation with the analyzed data which done by descriptively. This research to review management of the village fund which done by government at Sungai Ara and implement the principles of the village financial management as well as the settlement from obstacle within management village fund at Sungai Ara of year 2016.The result of this research indicate the management village fund at Sungai Ara of year 2016, has not been implemented effectively and efficiently, proved on year 2016 all of the implementation in construction the village not implemented accordance planning that done which caused the road cannot used by society, and also other obstacle such as less of understand about tupoksi as village government, less of communication and transparency to society.Keyword : Management, Village fund, Management of Village Fund